Diagnostic and Therapeutic Nanoparticles in Cardiovascular Diseases - D. Tyler, Patrick; M. Kang, Peter (Current Pharmaceutical Design, 2015)
Cardiovascular diseases are the major cause of non-communicable illness in both developing and developed nations, representing 30% of global deaths. New therapeutic approaches are desperately needed. Nanomedicine represents one such approach, and involves using molecular entities on the scale of 10-150 nanometers, for purposes of diagnosing, treating, and preventing disease. This review provides a basic overview of nanotechnology, then reviews specific applications of nanotechnology to cardiovascular diseases. Most research has focused on diagnosing and treating atherosclerosis using nanoparticles (NPs). However, researchers are beginning to study NPs for use in acute coronary syndromes, revascularization procedures, and heart failure. Antimicrobial NPs directed at biofilms likely have applicability to identifying and treating endocarditis. Despite the large disease burden of cardiovascular diseases, there are fewer researchers and less funding being applied to this research. Additional investment in NP therapies would pay great dividends once these therapies come of age.
Keywords: acute coronary system